2013
DOI: 10.1111/gcb.12362
|View full text |Cite
|
Sign up to set email alerts
|

Consistent response of vegetation dynamics to recent climate change in tropical mountain regions

Abstract: Global climate change has emerged as a major driver of ecosystem change. Here, we present evidence for globally consistent responses in vegetation dynamics to recent climate change in the world's mountain ecosystems located in the pan-tropical belt (30°N-30°S). We analyzed decadal-scale trends and seasonal cycles of vegetation greenness using monthly time series of satellite greenness (Normalized Difference Vegetation Index) and climate data for the period 1982-2006 for 47 mountain protected areas in five biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 72 publications
4
99
0
2
Order By: Relevance
“…In recent decades, global climate change has affected the characteristics of vegetation throughout the world [1,2]. As a key component of terrestrial ecosystems, vegetation has an irreplaceable role in regulating the carbon balance, reducing greenhouse gases, and maintaining climate stability by modifying biophysical land-surface properties and other biochemical processes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, global climate change has affected the characteristics of vegetation throughout the world [1,2]. As a key component of terrestrial ecosystems, vegetation has an irreplaceable role in regulating the carbon balance, reducing greenhouse gases, and maintaining climate stability by modifying biophysical land-surface properties and other biochemical processes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the relationships between vegetation activity and climate change have been carried out at different spatial scales (Krishnaswamy et al, 2014;Seddon et al, 2016). However, the specific variation in vegetation activity depends on 5 different environmental conditions and their changes.…”
mentioning
confidence: 99%
“…Although these tendencies were not very strong in terms of low R 2 values, the trajectories are extremely critical while facing future climate change. In a recent study of tropical mountain regions, Krishnaswamy et al (2014) [25] found mild greening trends followed by browning trends around the mid-1990s. They also observed strong associations between vegetation with increasing temperature and temperature-induced moisture stress from their study period of .…”
Section: Hcamentioning
confidence: 97%
“…Time series of NDVI data have proven to be an effective tool in assessing the phase of climate variability, and has been applied to worldwide geographical locations [3,[24][25][26][27][28][29]. NDVI data derived from the Advanced Very High Resolution Radiometer (AVHRR) onboard the National Oceanic and Atmospheric Administration's (NOAA) satellite series are widely used and have been considered as the best dataset available for long-term analysis of vegetation dynamics at reasonable spatial and temporal scales [30].…”
Section: Introductionmentioning
confidence: 99%